ANALYSIS OF THE INFLUENCE OF THE SCIENTIFIC APPROACH ON THE LEARNING ACHIEVEMENT OF READING AND WRITING THE QUR'AN IN GRADES V AND VI OF NGABLAK 1 PUBLIC ELEMENTARY SCHOOL, NGABLAK DISTRICT, MAGELANG REGENCY - Priarni, Rina; Matori; Imron, Ali; Indriyani, Dian; Zaman, Badrus (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to determine the results of the scientific approach, the improvement of the achievement of reading and writing the Qur'an, and its positive relationship with the learning achievement of these students. This study uses a quantitative research method, based on positivism, to investigate a specific population or sample. Data collection and analysis were carried out on individuals, groups, human environments, and social institutions. The research setting was determined by establishing good relationships with informants and maintaining distance from them, creating a natural situation. The setting consists of the place, actors, and activities. This study found that students were highly motivated and had a good scientific understanding, with a high level of active participation and goal achievement. The increase in learning achievement was also high, with an increase rate of 86.70%. The correlation coefficient between the two variables was positive, with a calculated rxy value of 0.941, which is greater than the table r value at the 5% significance level of 0.361. The Null Hypothesis (Ho) was rejected and the Alternative Hypothesis (Ha) was accepted, which indicates that students with high scientific achievement will achieve high learning achievement, while those with low scientific achievement will have low achievement